Management for Patient with Asthma in Lumbal Canal Stenosis Using General Anesthetic and Epidural Analgetic: A Case Report - Welly, Julian; Senapathi, Tjokorda Gde Agung (HM Publisher, 2023)
Background: Lumbar canal stenosis, which often occurs concurrently with degenerative spondylolisthesis (DS), is characterized by low back and leg pain. The treatment of high-degree spondylolisthesis is by surgery, which is a combination procedure of decompression and fusion. Surgical patients with a history of uncontrolled asthma three months before surgery had nearly double the risk of postoperative mortality. Case presentation: A 53-year-old male patient was diagnosed with Lumbal Canal Stenosis ec HNP at levels L2-l3, L3-l4, L4-l5, L5-s1 Spondylolisthesis at level L4-l5 Meyerding grade 1 Spondylosis Lumbalis. The patient has a history of mild intermittent bronchial asthma, which was diagnosed 2 years ago. The patient was planned for Decompression-Stabilization-Fusion surgery, with the anesthesia plan being general anesthesia prone position with epidural analgesia. Conclusion: Combined general anesthesia (GA) and epidural analgesia (EA) for major surgery due to excellent pain control, reduced perioperative morbidity, and even reduced mortality compared with systemic analgesia. For surgical patients who have a history of asthma, determining whether a patient's asthma is well-controlled or poorly controlled is key to mitigating perioperative complications.